Crystallite size distribution by two-dimensional XRD. Issue 2 (June 2022) - He, Bob B.
Abstract : The crystallite size distribution is an important parameter affecting the processing and properties of materials or products containing crystallites. The X-ray diffraction pattern collected with a two-dimensional detector may contain one or several spotty diffraction rings when an appropriate X-ray beam size is used. The spottiness of the diffraction ring is related to the size, size distribution, and orientation distribution of the crystallites. The intensity of a diffraction spot may represent its volume or size of a crystallite when a perfect Bragg condition is met. This paper introduces the algorithms and procedure to evaluate crystallite size distribution from a 2D diffraction pattern by rocking scan.